An Analysis of English Language Errors in Travel Brochures by students of SMKN 2 Maros - Muhammad Wahyu Anugrah; Batau, St. Haliah; Syam, Ulfa (Lembaga Jurnal FKIP Universitas Bosowa, 2024)
This study looks at how students at SMKN 2 Maros see English language mistakes in travel brochures. Using a simple research method, data were gathered through a questionnaire with 20 questions, answered by 52 students from classes X DKV, X ULP, and XI ULP. The results showed that most students (55%) often notice language mistakes in travel brochures, which affects how they understand and view the content. Even though there are many mistakes, most students (61.54%) said they usually understand the meaning of the words in the brochures. This means that while mistakes are common, they do not completely stop students from understanding. However, these mistakes do affect how trustworthy and reliable the brochures seem to the readers. The study suggests that fixing the English in travel brochures could make them work better and be more appealing. By reducing language mistakes, brochures can do a better job of attracting and informing potential travellers. This research shows how important it is to have correct and clear language in promotional materials, highlighting the need for good editing and proofreading when making travel brochures.